An association of intimate partner violence during the antenatal period with birth outcome: A longitudinal study - Arvind Sharma; Sunita Patel; Anant Kumar Lilhare; Kuldeep Singh Yadav; Jagmohan Singh Dhakar (Indian Journal of Community and Family Medicine)
Introduction: Intimate partner violence (IPV)/domestic violence is one of the most common types of violence against women. IPV during pregnancy is associated with a negative impact on birth outcome. It exerts adverse effects both upon physical and mental health status of women. Among physical it includes unintended pregnancy, sexually transmitted diseases and injuries, while among mental it includes depression, anxiety and stress. The risk of abortion, preterm birth, low birth weight babies, and intrauterine death are associated with IPV. This study was done with the objective to find out the association of IPV during the antenatal period with birth outcome. Material and Methods: This was a community-based longitudinal study conducted in the rural area of Jabalpur district (Madhya Pradesh). The duration of the study was 1 year (March 21–February 22). Two hundred and fifteen women in the third trimester of pregnancy were interviewed for IPV and their birth outcomes were assessed in subsequent visits of interview. IPV was assessed using the HURT, INSULT, THREATEN, and SCREAM scale (HITS scale) and birth outcome by predesigned questionnaire. Results: IPV was found among 28 (13%) women in the third trimester of pregnancy. One hundred and forty-nine (69.3%) newborns were term, whereas 56 (26%) newborns were preterm. Congenital disorder was found among 6 (2.8%) newborns. Strong and significant associations were found between pre-term delivery (aOR = 2.902, p = 0.0162), congenital disorder (aOR = 7.36, p = 0.034), and low birth weight (<2.5 kg) (aOR = 4.737, p = 0.0002) with IPV. Conclusion: IPV was a risk to the health of pregnant women and the birth outcome of pregnancy. Therefore, protection against IPV component should be implemented in various maternal and child programs for the betterment of maternal and fetal health from an early stage.